O18.3 Utility of Cerebrospinal Fluid Analysis in the Investigation and Treatment of Neurosyphilis. (13th July 2013) - Noy, M L; Rayment, M; Sullivan, A; Nelson, M
Abstract : Background: British guidelines detail indications for, and interpretation of, cerebrospinal fluid (CSF) examination in those diagnosed serologically with syphilis. We wished to evaluate our current clinical practise. Methods: We retrospectively studied all consecutive CSF syphilis tests performed in a large centre in London, UK, over five years. Indications for the examination, patient demographics, HIV metrics, serological tests for syphilis, and treatment regimens were examined. Results: A total of 291 CSF syphilis investigations were reviewed. 19% (n = 54) were requested to confirm or refute a diagnosis of neurosyphilis. Indications included serological diagnosis of syphilis plus symptoms: headache (28%), neurocognitive decline (9%), ophthalmological symptoms (18%), hearing loss (9%), other cranial nerve involvement (6%), psychosis (4%), and treatment failure (6%). Of this group, 37% (n = 20) were treated for neurosyphilis. 2% of those having had CSF examination for other indications were also treated for neurosyphilis (n = 5). All bar one patient were seropositive for syphilis. Of those treated for neurosyphilis (n = 25), all were HIV positive and 88% were male. Breakdown of CSF analysis revealed: CSF syphilis enzyme immunoassay (EIA) +/VDRL+ in 4%; EIA+/VDRL- in 56%; EIA-/VDRL- in 20%; and EIA equivocal/VDRL- in 20%. All patients in this group were treated in line with British guidelines. Of the 34 cases not treated for neurosyphilis, results were: EIA+/VDRL- in 35%; and EIA-/VDRL- in the remainder. No patient had a positive CSF VDRL in the absence of a negative CSF EIA. Conclusion: All patients with a positive VDRL in the CSF were treated for neurosyphilis, but this was a rare finding; 54% of patients who were CSF EIA+/VDRL- were treated for neurosyphilis. A proportion were treated for neurosyphilis despite CSF analysis refuting the diagnosis (EIA-). Cell counts, CSF chemistry, and clinical criteria may influence these differences. Further diagnostics may improve the sensitivity and specificity of CSF examination for neurosyphilis.